2001
DOI: 10.1073/pnas.98.4.2029
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging of cerebral activations and deactivations associated with hypercapnia and hunger for air

Abstract: There are defined medullary, mesencephalic, hypothalamic, and thalamic functions in regulation of respiration, but knowledge of cortical control and the elements subserving the consciousness of breathlessness and air hunger is limited. In nine young adults, air hunger was produced acutely by CO 2 inhalation. Comparisons were made with inhalation of a N2͞O2 gas mixture with the same apparatus, and also with paced breathing, and with eyes closed rest. A network of activations in pons, midbrain (mesencephalic teg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
135
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(147 citation statements)
references
References 34 publications
9
135
2
Order By: Relevance
“…Limbic areas, including the parahippocampal gyrus, insula, and cingulate gyrus, participate in emotive and visceral sensorimotor functions. Indeed, activation of these structures in response to respiratory challenges has been previously reported (5,8,11,31,35,47). The prefrontal cortex, including the middle and inferior frontal gyri, was also activated during respiratory challenge, as in previous studies (5,11,31,46).…”
Section: Activation In Cortical and Subcortical Regions Associated Wisupporting
confidence: 48%
See 2 more Smart Citations
“…Limbic areas, including the parahippocampal gyrus, insula, and cingulate gyrus, participate in emotive and visceral sensorimotor functions. Indeed, activation of these structures in response to respiratory challenges has been previously reported (5,8,11,31,35,47). The prefrontal cortex, including the middle and inferior frontal gyri, was also activated during respiratory challenge, as in previous studies (5,11,31,46).…”
Section: Activation In Cortical and Subcortical Regions Associated Wisupporting
confidence: 48%
“…This structure is also related to the control of certain autonomic (5), and emotion related to a need for air (11). Indeed, it has been demonstrated that the cingulate cortex has a complex and indirect relationship to central networks that control respiration (8,15). Therefore, we should expect that deactivation of the cingulate cortex might be observed in association with a relief from breathing difficulty by mandibular advancement.…”
Section: Deactivation In Cortical and Subcortical Regions Associated mentioning
confidence: 99%
See 1 more Smart Citation
“…The inhalation of CO 2 in man activates a pathway of responses that originate in the ventral medulla 21,43,44 and extend to the pons, midbrain, limbic and paralimbic areas, the parahippocampal and fusiform gyrus, and the anterior insula. 43,44 This physiological response network connects an element of basic respiratory control to the affective states of air hunger and fear that are promoted when respiratory disturbance becomes a salient element of consciousness. 43 However, functional imaging data show that activation of the limbic and cortical regions in man also depend upon subjective sensations of respiratory constraint and air hunger, as obtainable by the application to volunteers of a facemask for breathing.…”
Section: Pertinence To Human Panicmentioning
confidence: 99%
“…43,44 This physiological response network connects an element of basic respiratory control to the affective states of air hunger and fear that are promoted when respiratory disturbance becomes a salient element of consciousness. 43 However, functional imaging data show that activation of the limbic and cortical regions in man also depend upon subjective sensations of respiratory constraint and air hunger, as obtainable by the application to volunteers of a facemask for breathing. 43,44 There thus seem to be partially independent pathways that lead to limbic activation-and the corresponding emotions of anxiety or fear-in response to objective and perceived suffocation.…”
Section: Pertinence To Human Panicmentioning
confidence: 99%